The importance of developing listening comprehension skills - Aripova, Nasiba (The Lingua Spectrum, 2024)
This article is dedicated to studying the use of strategies and methods for activating and developing listening comprehension skills in a foreign language. Thus, working with each language skill, shaping and integrating them, forms the foundation of modern methodology. From this perspective, explaining the importance of listening comprehension skills and working with them is crucial. Additionally, the article focuses on the significance of listening comprehension for English language learners and analyzes and implements effective methods for utilizing interactive audio-visual tools to improve and develop these skills in the classroom. Several methods can be applied in practice to form and develop listening comprehension in modern English, most of which are carried out in an integrated manner with other skills. In language learning, every learner must develop four skills, one of which is listening to the speaker and accurately receiving the information provided, followed by responding appropriately. Therefore, the article emphasizes the importance of using interactive methods and selecting online education platforms correctly to improve this skill and achieve effective results. Furthermore, the importance of developing listening skills and the challenges faced in listening comprehension are explored and analyzed.